1996
DOI: 10.1002/j.1550-8528.1996.tb00506.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Visceral Adipose Tissue and Improvement of Metabolic Indices: Effect of Dexfenfluramine in NIDDM

Abstract: Res. 1996;4:1-7. Increased visceral adipose tissue is thought to contribute to impaired glucose tolerance. We studied 10 men with non-insulin dependent diabetes (NIDDM) before and after a 12-week intervention study using dexfenfluramine. Subjects had a mean body mass index (BMI) of 26.4 ± 1.7 kg\m 2 and had an abdominal distribution of body fatness (waist-to hip ratio >0.9). Anthropometric indices, biochemistry, macronutrient intake from 7-day food records as well as a euglycaemic glucose clamp and magnetic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0
2

Year Published

1996
1996
2003
2003

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 16 publications
2
36
0
2
Order By: Relevance
“…The fact that men in the present study lost more fat from the VAT compartment than from the SAT depot is in accordance with other clinical trials which also used drug therapy to induce weight loss (Marks et al, 1996(Marks et al, ,1998. In the study of Marks et al, (1998) placebo-treated men lost significantly less VAT than men who received the dexfenfluramine treatment.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The fact that men in the present study lost more fat from the VAT compartment than from the SAT depot is in accordance with other clinical trials which also used drug therapy to induce weight loss (Marks et al, 1996(Marks et al, ,1998. In the study of Marks et al, (1998) placebo-treated men lost significantly less VAT than men who received the dexfenfluramine treatment.…”
Section: Discussionsupporting
confidence: 90%
“…This observation is in accordance with two other recent studies that reported differences of the same magnitude (Goodpaster et al, 1999;Wirth & Steinmetz, 1998). However, it has been suggested that individuals who display large initial amounts of VAT are also characterized by a more substantial reduction of this depot during weight loss interventions Leenen et al, 1992;Marks et al, 1996Marks et al, ,1998. Since men in the present study displayed VAT levels that were higher than those measured in women, initial levels of VAT were also considered as a potential covariate of the changes of VAT which occurred in response to weight loss.…”
Section: Dependent Variablesupporting
confidence: 92%
See 1 more Smart Citation
“…INCREASED INTRA-ABDOMINAL ADIPOSE TISSUE (IAAT) has been linked to metabolic perturbations, especially hyperlipidemia and insulin resistance (21,23), and reduction of intra-abdominal fat has been shown to improve insulin sensitivity in both animals (2) and humans (17,26). A substantial proportion of human immunodeficiency virus (HIV)-infected individuals on highly active antiretroviral therapy (HAART) develop fat redistribution, or HIV lipodystrophy, which is characterized by increased IAAT and/or depletion of subcutaneous adipose tissue (3)(4)(5).…”
mentioning
confidence: 99%
“…31 Another study demonstrated that dexfen¯ur-amine preferentially reduces abdominal fat and, therefore, may have a special potential in the treatment of obese subjects with the metabolic syndrome. 32 However, due to possible serious adverse effects on heart valves, fen¯uramine and dexfen¯uramine were withdrawn in 1997. 24 Fluoxetine selectively inhibits the central reuptake of serotonin and is widely used as an antidepressant drug.…”
Section: Serotoninergic Agentsmentioning
confidence: 99%